A Vision of a Missionary Parish - Heriyanto, I Wayan (Perspektif, 2024)
This article discusses and explores the vision of a missionary parish. It does so in three sections: First, it discusses the understanding of a missionary parish based on a scriptural foundation in the Acts of the Apostles, the Pauline metaphor of the Body of Christ, and Paul’s strategy of mission. Second, it presents Pope Francis’ insights on the theme of the missionary parish in his apostolic exhortation, Evangelii Gaudium. Third, it explores the ideas of four contemporary missiologists and theologians regarding the missionary Church and its implications for the understanding of a missionary parish.